Scleral birefringence as measured by polarization-sensitive optical coherence tomography and ocular biometric parameters of human eyes in vivo - 福田 慎一; 石井 晃太郎; 大鹿 哲郎; 安野 嘉晃; Yamanari Masahiro; Nagase Satoko; Fukuda Shinichi; Ishii Kotaro; Tanaka Ryosuke; Yasui Takeshi; Oshika Tetsuro; Miura Masahiro; et al. (Biomedical Optics Express, 2014)
The relationship between scleral birefringence and biometric parameters of human eyes in vivo is investigated. Scleral birefringence near the limbus of 21 healthy human eyes was measured using polarization-sensitive optical coherence tomography. Spherical equivalent refractive error, axial eye length, and intraocular pressure (IOP) were measured in all subjects. IOP and scleral birefringence of human eyes in vivo was found to have statistically significant correlations (r = −0.63, P = 0.002). The slope of linear regression was −2.4 × 10−2 deg/μm/mmHg. Neither spherical equivalent refractive error nor axial eye length had significant correlations with scleral birefringence. To evaluate the direct influence of IOP to scleral birefringence, scleral birefringence of 16 ex vivo porcine eyes was measured under controlled IOP of 5−60 mmHg. In these ex vivo porcine eyes, the mean linear regression slope between controlled IOP and scleral birefringence was −9.9 × 10−4 deg/μm/mmHg. In addition, porcine scleral collagen fibers were observed with second-harmonic-generation (SHG) microscopy. SHG images of porcine sclera, measured on the external surface at the superior side to the cornea, showed highly aligned collagen fibers parallel to the limbus. In conclusion, scleral birefringence of healthy human eyes was correlated with IOP, indicating that the ultrastructure of scleral collagen was correlated with IOP. It remains to show whether scleral collagen ultrastructure of human eyes is affected by IOP as a long-term effect.